Mangiferin activates the Nrf2-ARE pathway and reduces etoposide-induced DNA damage in human umbilical cord mononuclear blood cells. (April 2015) - Zhang, Benping; Zhao, Jie; Li, Shanshan; Zeng, Linglan; Chen, Yan; Fang, Jun
Abstract Context: Mangiferin (2-C-β-d-gluco-pyranosyl-1, 3, 6, 7-tetrahydroxyxanthone) is a well-known natural antioxidant distributed in various plants of the Anacardiaceae and Gentianaceae families. Mangiferin can inhibit carcinogen-induced lung or colon tumor formation in experimental animals. However, the molecular mechanisms of its chemopreventive activity remain unexplored. Objective: This study aimed to investigate the effects of mangiferin on chemical carcinogen-induced DNA damage and Nrf2-ARE signaling in hematopoietic cells. Materials and methods: Mononuclear cells (MNCs) were isolated from human umbilical cord blood (hUCB). DNA damage was evaluated by comet and micronucleus assays. The expression of Nrf2 and NQO1 was examined by immunofluorescence and western blotting. An electrophoretic mobility shift assay (EMSA) was used to detect the binding activity of Nrf2 with NQO1-ARE sequences. Results: We found that mangiferin treatment significantly reduced DNA damage in etoposide-treated MNCs, which was verified by decreased olive tail moment (OTM) and micronucleus (MN) frequency. Mangiferin treatment significantly promoted Nrf2 translocation into the nucleus and increased nuclear Nrf2 expression. Moreover, NQO1, an Nrf2 signaling target, was significantly upregulated by mangiferin treatment, and the binding activity of Nrf2 with NQO1-ARE sequences was elevated after mangiferin treatment. Discussion and conclusion: Mangiferin activated Nrf2 signaling, upregulated NQO1 expression, and significantly reduced etoposide-induced DNA damage. Thus, mangiferin is a potential cytoprotective agent for hematopoietic cells.